1994
DOI: 10.1002/aqc.3270040105
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fractionation and mobility in Loch Leven sediments

Abstract: ABSTRACT1. This paper reports on the application of a chemical fractionation scheme for assessing the amounts, forms and potential mobility (recycling potential) of phosphorus in the sediments of the freshwater Loch Leven, which is currently highly topical in relation to eutrophication and its manifest dense, potentially toxic, blue-green algae. The findings are placed in the context of the biological importance of the loch, the problems it is experiencing and some management options for its restoration.2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…However, prolonged internal loading coupled with a low flushing rate (2-3 lake volumes per year) resulted in poor water quality being maintained, with an improvement in water column SRP concentration only being observed in recent years (Carvalho & Kirika, 2003). This improvement in water quality has not been mirrored in the sediment P composition (Farmer et al, 1994;Spears et al, 2006). Field measurements, water chemistry, and sediment P fractionation Monthly sampling was conducted between April 2004 and April 2005 from six sites along a depth transect (2, 2.5, 3.5, 5.5, 10, 22 m overlying water depth), to allow comparison of shallow and deep regions of the loch throughout the year.…”
Section: Study Sitementioning
confidence: 82%
See 1 more Smart Citation
“…However, prolonged internal loading coupled with a low flushing rate (2-3 lake volumes per year) resulted in poor water quality being maintained, with an improvement in water column SRP concentration only being observed in recent years (Carvalho & Kirika, 2003). This improvement in water quality has not been mirrored in the sediment P composition (Farmer et al, 1994;Spears et al, 2006). Field measurements, water chemistry, and sediment P fractionation Monthly sampling was conducted between April 2004 and April 2005 from six sites along a depth transect (2, 2.5, 3.5, 5.5, 10, 22 m overlying water depth), to allow comparison of shallow and deep regions of the loch throughout the year.…”
Section: Study Sitementioning
confidence: 82%
“…Inorganic nutrient analyses were carried out using the methods of Wetzel and Likens (2000). Sediment P fractionation was carried out using a sequential chemical extraction technique based on Psenner et al (1988) and Farmer et al (1994). Two sub-samples of homogenised slurry, from each site, were subject to the following extraction procedure on each sample date: (1) repeated extraction in 1 M NH 4 Cl for 2 h and quantification of SRP [labile P]; (2) repeated extraction with 0.11 M NaHCO 3 /0.11 M Na 2 S 2 O 4 for 1 h and quantification of SRP [reductantsoluble P] and total soluble phosphorus (TSP) [reductant-soluble soluble un-reactive phosphorus (SURP)]; (3) repeated (for 1 h) extraction in 1 M NaOH for 18 h followed by quantification of SRP (metal-oxide adsorbed P), and TSP; (4) repeated (for 1 h) extraction with 0.5 M HCl for 18 h and quantification of SRP [apatite-bound P]; (5) digestion with 30% (v/v) H 2 SO 4 and 8% K 2 S 2 O 4 at 121°C for 30 min followed by SRP quantification [residual P].…”
Section: Study Sitementioning
confidence: 99%
“…that associated with Fe and, therefore, releasable under reducing conditions) in the upper 4 cm of sediment was about 20 t P. Using a water column mass balance approach they also estimated that P cycling between the sediments and the water column amounted to a maximum sediment uptake of 136 kg TP day -1 , a maximum sediment release of 88 kg TP day -1 . Advances in chemical speciation techniques facilitated a more comprehensive assessment of sediment P fractions in 1990, immediately 1967 1968 1969 1970 1971 1972 1973 1974 1975 1976 1977 1978 1979 1980 1981 1982 1983 1984 1985 1986 1987 1988 1989 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 , 1968-2008 after significant P loading reductions (Farmer et al, 1994). The authors found that a large proportion (*30%) of the 68.8 t of TP contained in the upper 4 cm of sediments within the loch was release sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect effect of an algal bloom on the behavior of Mn has also been suggested as a possible cause of Mn nodule formation in freshwater, eutrophic Lake Oneida, New York (Dean and Greeson 1979;Dean et al 1981). Because Fe and P are known to be released from Loch Leven sediments during calm, warm weather conditions (Farmer et al 1994), it might be anticipated that Mn would also be released under such conditions. The greater Mn inventory in the summer core, however, indicates that the reprecipitation and sedimentation of Mn must outweigh any release from the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Chl a levels can reach 160 pg liter-' in summer. Summer algal blooms are a subject of concern due to potential harmful effects of toxins released by blue-green algae in this loch, which is famous for trout fishing (Bailey-Watts et al 1994). Water column stratification is relatively uncommon, intermittent, and affects only the deep kettle holes (22-23 m).…”
Section: Loch Lomond-lochmentioning
confidence: 99%